(untitled) (Research, Society and Development, 2021)
Camu-camu is an exotic fruit, known for having high concentrations of vitamin C and bioactive compounds. In order to diversify the consumption of this fruit, this study developed milk ice cream formulations and evaluated the effect of the addition of different concentrations of camu-camu pulp (20 to 26%), sugar (12 to 14%) and defatted dry extract (DDE) (12 to 16%) through a mixture design. Ice creams were evaluated by analyses of overrun, density, melting time, ratio, and cost. Three formulations were defined based on maximum melting time and ratio and minimum cost. The ice creams formulations defined by the experimental design consisted of the following proportions of pulp, sugar and DDE (%): 26:12:12, 20:14:16 and 24:14:12. These formulations were evaluated in relation to their physicochemical and technological characteristics, antioxidant and reducing capacity and sensory acceptance. The results showed that all formulations had high concentrations of antioxidant compounds and vitamin C and the formulation with the addition of camu-camu pulp lower than 24% had greater sensory acceptance. Therefore, it is concluded that the addition of camu-camu pulp in milk ice cream is interesting from a nutritional point of view, as it can increase the content of nutrients and minerals in the final blend.